2016
DOI: 10.4103/1817-1745.181252
|View full text |Cite
|
Sign up to set email alerts
|

Rare clinical presentation of diffuse large B-cell lymphoma as otitis media and facial palsy

Abstract: Extra nodal presentation of Non Hodgkins Lymphoma (NHL) is a rare entity, and data available about the NHL that primarily involves of middle ear and mastoid is limited. We report a case of diffuse large B cell lymphoma (DLBCL), in a 2 year 8 month old boy, who developed otalgia and facial palsy. Computed tomography revealed a mass in the left mastoid. Mastoid exploration and histopathological examination revealed DLBCL. This case highlights the importance of considering malignant lymphoma as one of the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Our review shows that a wide variety of lymphoma subtypes can occur in the middle ear and can be either primary or secondary malignancy. Most patients diagnosed with NHL DLBCL of the middle ear are male adults, with one case reported in a two-year-old [ 4 ]. It is also observed that most patients present with symptoms of otalgia, otorrhoea, hearing loss, and facial palsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review shows that a wide variety of lymphoma subtypes can occur in the middle ear and can be either primary or secondary malignancy. Most patients diagnosed with NHL DLBCL of the middle ear are male adults, with one case reported in a two-year-old [ 4 ]. It is also observed that most patients present with symptoms of otalgia, otorrhoea, hearing loss, and facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is the most common site of presentation of NHL, followed by the head and neck region. Involvement of the middle ear and temporal bone is rare, and few cases have been reported in the literature [ 2 - 4 ]. We present a case of extra-nodal DLBCL involving the middle ear and the challenges faced while managing the patient with a literature review on the disease.…”
Section: Introductionmentioning
confidence: 99%
“… 3 In people, there are <30 cases of lymphoma of the middle ear reported in the medical literature. 7 13 Review of these cases suggests that non-Hodgkin lymphoma is most common, with an approximately equal distribution of B-cell and T-cell neoplasms. There are no reports of lymphoma affecting the middle ear in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this appears to be a key historical component in nearly all previously reported cases of middle-ear lymphoma in cats and people. 1 – 3 , 6 , 7 , 10 12 A large majority of people entered remission once an accurate diagnosis was made and treatment was initiated. Thus, cases with presumed or confirmed chronic otitis media/interna that lack adequate response to antimicrobial therapy warrant further investigation to limit delay of appropriate treatment and prevent further progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…When the 24 literature cases were combined with our case, 4 classifications of lymphoid neoplasms associated with the temporal bone were noted, including 7 cases of B cell lymphoma, [6][7][8][9][10][11][12] 4 T cell lymphomas, [13][14][15][16] 4 BLs, [17][18][19] and 10 leukemias. [20][21][22][23][24][25] 17 of 25 patients were male.…”
Section: Literature Reviewmentioning
confidence: 99%